2010
DOI: 10.1016/j.cardfail.2010.07.249
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cardiomyopathy

Abstract: Individuals with diabetes are at a significantly greater risk of developing cardioymyopathy and heart failure despite adjusting for concomitant risks such as coronary artery disease or hypertension. This has led to the increased recognition of a distinct disease process termed as "diabetic cardiomyopathy." In this article, we perform an extensive review of the pathogenesis and treatment of this disease. From a clinical perspective, physicians should be aware of this entity, and early screening should be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 93 publications
0
79
0
2
Order By: Relevance
“…The natural history of DCM consists of a latent subclinical period, during which cellular structural insults and abnormalities occur initially leading to diastolic dysfunction and progressing to degenerative changes, which the myocardium is unable to repair, with subsequent irreversible pathological remodeling [15]. Recent echocardiographic modalities (tissue Doppler and 2-dimensional longitudinal strain) represent a diagnostic method that can help in early detection of DCM and can evaluate diastolic and systolic heart dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of DCM consists of a latent subclinical period, during which cellular structural insults and abnormalities occur initially leading to diastolic dysfunction and progressing to degenerative changes, which the myocardium is unable to repair, with subsequent irreversible pathological remodeling [15]. Recent echocardiographic modalities (tissue Doppler and 2-dimensional longitudinal strain) represent a diagnostic method that can help in early detection of DCM and can evaluate diastolic and systolic heart dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic cardiomyopathy, a complication causing heart failure, can occur independently of vascular complications, such as coronary artery disease and hypertension, thus representing a distinct disease process (Francis, 2001;Murarka and Movahed, 2010). The mechanism by which diabetes causes cardiomyopathy remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia leads to an increase in oxidative stress by exacerbating glucose oxidation and mitochondrial generation of reactive oxygen species (ROS) which cause DNA damage and contributes to accelerated apoptosis. Also increased ROS activate poly (ADP ribose) polymerase (PARP) as a reparative enzyme (4). PARP inhibits glyceraldehyde phosphate dehydrogenase (GADPH), diverting glucose from its glycolytic pathway and into alternative biochemical pathways that are considered to be the mediators of hyperglycemiamediated cellular injury.…”
Section: Hyperglycemia and Hyperinsulinemiamentioning
confidence: 99%
“…Although coronary artery disease (CAD) is very common, heart failure (HF) is also a major cause of mortality and morbidity in patients with diabetes mellitus (3). In addition, diabetic individuals are under increased risk for HF development after adjusting concomitant risk factors such as hypertension and CAD (4,5). The Framingham study, United Kingdom Prospective Diabetic Study and Euro Heart Failure Survey all suggested that the presence of diabetes may independently increase the risk of developing HF.…”
Section: Introductionmentioning
confidence: 99%